2022
DOI: 10.3390/microorganisms10101995
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Microbiome of Fecal Samples Obtained from Adolescents with Different Weight Conditions on Resistance Gene Transfer

Abstract: Antimicrobial resistance (AMR) is a relevant public health problem worldwide, and microbiome bacteria may contribute to the horizontal gene transfer associated with antimicrobial resistance. The microbiome of fecal samples from Mexican adolescents were analyzed and correlated with eating habits, and the presence of AMR genes on bacteria in the microbiome was evaluated. Fecal samples from adolescents were collected and processed to extract genomic DNA. An Illumina HiSeq 1500 system was used to determine resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…To better understand the effect of the PPFA on the gut microbial community and how the gut microbiota further influence the growth performance and carcass traits in fattening pigs, the culture-based broad microbial counts were complemented with a highly detailed metagenomic analysis of the fecal samples [25]. In agreement with our results, many studies [58,59] have reported that Firmicutes and Bacteroidetes were the two most abundant families in all porcine fecal samples. The average abundance of Firmicutes in the T and C group samples (the samples were collected at the end of the trial) was significantly higher than that in the S group samples (the samples were collected at the beginning of the trial from both groups), but Bacteroidetes presented the opposite trend.…”
Section: Discussionsupporting
confidence: 81%
“…To better understand the effect of the PPFA on the gut microbial community and how the gut microbiota further influence the growth performance and carcass traits in fattening pigs, the culture-based broad microbial counts were complemented with a highly detailed metagenomic analysis of the fecal samples [25]. In agreement with our results, many studies [58,59] have reported that Firmicutes and Bacteroidetes were the two most abundant families in all porcine fecal samples. The average abundance of Firmicutes in the T and C group samples (the samples were collected at the end of the trial) was significantly higher than that in the S group samples (the samples were collected at the beginning of the trial from both groups), but Bacteroidetes presented the opposite trend.…”
Section: Discussionsupporting
confidence: 81%